1992
DOI: 10.1007/bf01203756
|View full text |Cite
|
Sign up to set email alerts
|

The effect of caffeine on the ability of spermatozoa to fertilize mature human oocytes

Abstract: Although caffeine has been reported to enhance spermatozoon motility as well as fertilizing ability, its use in clinical practice has remained sparse. We report here the results carried out to assess the effect of exposing normal human spermatozoa to different concentrations of caffeine on their motility, their ability to fertilize oocytes, and the subsequent development of resulting embryos. Mature human oocytes were inseminated with spermatozoa washed and capacitated in 1.25, 2.5, and 5 mM caffeine. The fert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Treatment of sperm with caffeine is common in some hooved species, and while treatment improves IVF rates it can also decrease the rate of blastocyst formation (Tatham et al, 2003;Mao et al, 2005). Like wise, treatment of human sperm with caffeine to improve motility for IVF resulted in delayed embryo development compared to IVF with untreated sperm (Imoedemhe et al, 1992). Similarly, pronuclear mouse embryos incubated with low levels of caffeine (0.16 mM) frequently stopped developing after one to three cell cycles (Scott and Smith, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of sperm with caffeine is common in some hooved species, and while treatment improves IVF rates it can also decrease the rate of blastocyst formation (Tatham et al, 2003;Mao et al, 2005). Like wise, treatment of human sperm with caffeine to improve motility for IVF resulted in delayed embryo development compared to IVF with untreated sperm (Imoedemhe et al, 1992). Similarly, pronuclear mouse embryos incubated with low levels of caffeine (0.16 mM) frequently stopped developing after one to three cell cycles (Scott and Smith, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, spermatozoa pre-incubated with caffeine showed a significant decrease in the percentage of penetrated zona-free hamster oocytes [117]. The only study available [118] that investigated the effect of caffeine in assisted reproduction using 42 oocytes from 21 women showed an increase in sperm motility but a significant decrease in the fertilization rates and embryo development.…”
Section: In Vitro Treatment Of Spermatozoamentioning
confidence: 99%
“…In one humped camels, El‐Bahrawy () reported that addition 4 mM of caffeine improved sperm kinetics and physical semen characteristics post‐thaw including PG, VCL. Imoedemhe, Sigue, Pacpaco, and Olazo () recorded that caffeine supplementation improved VCL VSL, VAP, LIN, and STR patterns and LIN in fresh human sperm. Yeste et al.…”
Section: Discussionmentioning
confidence: 99%